The External Impact of China's Exchange Rate Policy : Evidence From Firm Level Data - Eichengreen, Barry (IMF Working Papers; Working Paper ;, 2011)
We examine the impact of renminbi revaluation on foreign firm valuations, considering two surprise announcements of changes in China's exchange rate policy in 2005 and 2010 and employing data on some 6,000 firms in 44 economies. Stock returns rise with renminbi revaluation expectations. This reaction appears to reflect a combination of improvements in general market sentiment and specific trade effects. Expected renminbi appreciation has a positive effect on firms exporting to China but a negative impact on those providing inputs for the country's processing exports. Stock prices rise for firms competing with China in their home market but fall for firms importing Chinese products with large imported-input content. There is also some evidence that expected renminbi appreciation reduces the valuation of financially-constrained firms, presumably because appreciation implies reduced Chinese purchases of foreign securities. The results carry over when we consider ten instances of market-perceived changes in prospective Chinese currency policy.